Autophagic Regulation of Lipid Homeostasis in Cardiometabolic Syndrome - Yang, Mingjie; Zhang, Yingmei; Ren, Jun (Frontiers in Cardiovascular Medicine, 2018)
As an important protein quality control process, autophagy is essential for the degradation and removal of long-lived or injured cellular components and organelles. Autophagy is known to participate in a number of pathophysiological processes including cardiometabolic syndrome. Recent findings have shown compelling evidence for the intricate interplay between autophagy and lipid metabolism. Autophagy serves as a major regulator of lipid homeostasis while lipid can also influence autophagosome formation and autophagic signaling. Lipophagy is a unique form of selective autophagy and functions as a fundamental mechanism for clearance of lipid excess in atherosclerotic plaques. Ample of evidence has denoted a novel therapeutic potential for autophagy in deranged lipid metabolism and management of cardiometabolic diseases such as atherosclerosis and diabetic cardiomyopathy. Here we will review the interplays between cardiac autophagy and lipid metabolism in an effort to seek new therapeutic options for cardiometabolic diseases.